Alternative splicing of tumour-related rac1b is regulated by upstream signalling pathways - Gonçalves, Vânia (2012)
The small GTPase Rac1 regulates signalling pathways controlling actin-dependent cell motility as well as gene transcription. Analternative splicing variant Rac1b is overexpressed in a subset of colorectal tumours and cooperates with mutant B-Raf to sustain tumour cellviability. The alternative splicing mechanism regulating Rac1b expression involves two antagonistic splicing factors, ASF/SF2 and SRp20. Using aRac1 minigene approach and siRNA-mediated depletion, we identified ASF/SF2 as an enhancer of endogenous Rac1b splicing whereas SRp20 actsas a silencer. Inhibition of the PI3-kinase pathway increased protein levels of ASF/SF2 and promoted Rac1b generation. By contrast, depletion ofendogenous protein kinase SRPK1 led to decreased Rac1b expression. Together, these data indicate that altered upstream signaling pathways incolorectal cancer cells will target splicing factors that regulate alternative splicing of the small GTPase Rac1.